Diseño y construcción de un banco para la obtención de las curvas características de una bomba centrifuga Universidad Antonio Nariño sede Neiva, Buganviles (2023)
This degree project aims to provide a didactic bench for obtaining the characteristic curves of a centrifugal pump for the Mechanical Engineering laboratory of the Antonio Nariño University, Neiva campus. This tool will strengthen the educational practices of teachers and students, who need to supplement these activities with theory, virtual simulators and lectures. Due to the lack of a bench that simulates the operation of a centrifugal pump, in order to achieve the learning in an experimental way for the subject of hydraulic machines. The objective is the design and construction of a bench and laboratory guides, to obtain the characteristic curves of a centrifugal pump, with an experimental methodology, through the programming of sensors and the parameterization of variables in an Excel spreadsheet, represent the representative graphs proposed in this project and also allow the calculations: power, efficiency and NPSH, based on the variation of the flow. It is expected as a result of implementing this didactic tool, to reach the competences of interpreting and analyzing the theoretical and practical data on the design and installation of a centrifugal pump.